1H, 13C and 15N NMR assignments of self-incompatibility protein homologue 15 from Arabidopsis thaliana - Coulthard, R; Rajasekar, K; Ride, J; Hyde, E; Smith, L (Springer Netherlands, 2018)
The SPH proteins are a large family of small, disulphide-bonded, secreted proteins, originally found to be involved in the self-incompatibility response in the field poppy (Papaver rhoeas). They are now known to be widely distributed in plants, many containing multiple members of this protein family. Apart from the PrsS proteins in Papaver the function of these proteins is unknown but they are thought to be involved in plant development and cell signalling. There has been no structural study of SPH proteins to date. Using the Origami strain of E. coli, we cloned and expressed one member of this family, SPH15 from Arabidopsis thaliana, as a folded thioredoxin-fusion protein, purified it from the cytosol, and cleaved it to obtain the secreted protein. We here report the assignment of the NMR spectra of SPH15, which contains 112 residues plus three N-terminal amino acids from the vector. The secondary structure propensity from TALOS+ shows that it contains eight beta strands and connecting loops. This is largely in agreement with predictions from the amino acid sequence, which show an additional C-terminal strand.